The quality of the physical environment of outdoor academies - Maia, Marina Lisboa [UNESP]; de Castro Fontes, Maria Solange Gurgel [UNESP]; Magagnin, Renata Cardoso [UNESP] (My University, 2020)
Outdoor gyms (AAL's) are contemporary urban infrastructures designed to encourage physical exercise in open spaces, whether public or private. They exert an influence on the urban environment and provide a broad field of research, especially related to the impact on people's quality of life. This impact requires academies endowed with a quality physical environment, be it in its base, border and surroundings. In this context, this paper shows a method to evaluate the quality of the AAL's base, applied in 10 academies in Bauru-SP, Brazil. The results highlight aspects related to the themes Accessibility, Comfort, Uses and Activities and Sociability, which favor and/or compromise the quality of the physical environment, and show that the proposed method is an effective tool for: 1. Use in interventions in the AAL's evaluated; 2. Planning of similar spaces and 3. Comparison between different AAL's.
A qualidade do ambiente físico de academias ao Ar livre
Keywords: Open public spaces; Outdoor gyms; Quality index of the physical environment